Effects of Communication Company’s Safety Management System on Workers" Safety Consciousness and Safety Observance Behavior - JIn-Woo Jung; Kwang-Seup Byun (Journal of Information and Communication Convergence Engineering, 19(2), 2021)
In this study, the effect of a telecommunication company’s safety management system on workers' safety awareness and safety behavior was empirically verified. The main findings are as follows: First, among the factors of the telecommunication company's safety management system, the management supervisor's capability and level of industrial accident investigations were found to have a significant positive effect on workers' safety awareness. Second, workers’ safety awareness was observed to exert a significant positive effect on their safety behavior. Third, among the factors of the telecommunication company's safety management system, the management supervisor’s capability and industrial accident investigations were found to have a significant positive effect on the safety behavior of workers. Fourth, although the telecommunications safety management system factors, such as management supervisors’ capability and industrial accident investigations, were found to have a positive effect on workers' safety awareness, they had no mediated effect on workers' safety behavior through safety awareness. KCI Citation Count: 0